Comparative policy studies conceptual and methodological challenges - Engeli, Isabelle; Allison, Christine Rothmayr; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
In the first volume of its kind, a collection of top policy scholars combine empirical and methodological analysis in the field of comparative policy studies to provide compelling insights into the formulation, implementation and evaluation of policies across regional and national boundaries.
Keywords: Science; Science; Science, general